2003
DOI: 10.1002/jcb.10716
|View full text |Cite
|
Sign up to set email alerts
|

Membrane actions of vitamin D metabolites 1α,25(OH)2D3 and 24R,25(OH)2D3 are retained in growth plate cartilage cells from vitamin D receptor knockout mice

Abstract: 1alpha,25(OH)(2)D(3) regulates rat growth plate chondrocytes via nuclear vitamin D receptor (1,25-nVDR) and membrane VDR (1,25-mVDR) mechanisms. To assess the relationship between the receptors, we examined the membrane response to 1alpha,25(OH)(2)D(3) in costochondral cartilage cells from wild type VDR(+/+) and VDR(-/-) mice, the latter lacking the 1,25-nVDR and exhibiting type II rickets and alopecia. Methods were developed for isolation and culture of cells from the resting zone (RC) and growth zone (GC, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 59 publications
3
55
1
Order By: Relevance
“…We have shown here that, similarly to rat growth plate chondrocytes at proliferative stages (36), late differentiation of cranial cells still can be restrained by 1,25-dihydroxyvitamin D3. It has been shown previously (37) that rat costal chondrocytes are capable of producing this vitamin D metabolite, which eliminates the necessity of availability of the systemic vitamin D hormone.…”
Section: Discussionmentioning
confidence: 61%
“…We have shown here that, similarly to rat growth plate chondrocytes at proliferative stages (36), late differentiation of cranial cells still can be restrained by 1,25-dihydroxyvitamin D3. It has been shown previously (37) that rat costal chondrocytes are capable of producing this vitamin D metabolite, which eliminates the necessity of availability of the systemic vitamin D hormone.…”
Section: Discussionmentioning
confidence: 61%
“…This was unanticipated since studies using rat [Schwartz et al, 1988[Schwartz et al, , 1995 and mouse [Boyan et al, 2003] costochondral growth plate chondrocytes have shown that resting zone cells are the primary target for 24R,25(OH) 2 D 3 , whereas prehypertrophic and hypertrophic chondrocytes are primary targets for 1a,25(OH) 2 D 3 . Moreover, 20 mM Pi induced sensitivity of the ATDC5 cells to 10 À7 M 24R,25(OH) 2 D 3 , which is the concentration at which costochondral resting zone cells exhibit maximal responses to the seco-steroid [Boyan et al, 2003] and similar to the level of endogenous 24R,25(OH) 2 D 3 produced by these cells when stimulated in culture . h on day 10 and day 11 and RT-PCR was performed to assess mRNA expression of collagen types I, II, and X and also SOX9, COMP, and aggrecan (AGG).…”
Section: Discussionmentioning
confidence: 94%
“…Previous work examining mouse and rat growth plates has shown that two metabolites of vitamin D,24,25(OH) [Boyan et al, , 2003. Chondrocytes from the resting zone exhibit specific sensitivity to 24,25(OH) 2 D 3 , whereas cells in the growth zone no longer exhibit the same responses to 24,25(OH) 2 D 3 but have acquired specific sensitivity to 1,25(OH) 2 D 3 .…”
mentioning
confidence: 95%
“…As global knockout of Pdia3 is embryologically lethal, the ability to determine its full impact is hampered. However, chondrocytes isolated from costochondral cartilage of VDR knockout mice and Ca 2+ influx studies in the guts of these mice demonstrate that 1α,25(OH) 2 D 3 still elicits rapid activation of PKC and a biological response [38,39]. Studies using Pdia3 conditional knockout mice [40], Pdia3-silenced osteoblasts [41], and Pdia3 ± heterozygote mice [42] have demonstrated a loss of rapid activation of PKC and release of PGE 2 , decreased osteopontin production and alkaline phosphatase activity, and bone and cartilage abnormalities.…”
Section: Alternative Membrane Receptorsmentioning
confidence: 98%